Sacrament : a novel - Straight, Susan (Counterpoint, 2025)
"In August 2020, a group of nurses are working in the ICU at a hospital in San Bernardino at the height of a Covid surge: Larette Embers, whose husband, Grief, is an animal control officer; Cherrise Martinez, whose husband died years ago in a car crash, and whose daughter Raquel has been sent to a Coachella date farm to live with her great-aunt to avoid the virus; and Marisol Manalang, born in the Philippines but based in Sacramento. To safeguard their families, the nurses are living in a makeshift RV camp close to the hospital; they share food and cigarettes yet keep their work private. For this is a country in crisis, and they are assisting strangers at the edge of death with infinite tenderness and growing desperation. As the nurses struggle with the skyrocketing number of sick patients, Cherisse's daughter goes missing. Grief's friend Johnny Frias, a California Highway Patrol officer, joins the search to find her, and the resulting journey leads to new love and loss, pushing all our characters to their breaking points"--